Regional Income and its Convergence in Indonesia - Kurniawati, Sri (International Journal of Economics and Financial Issues, 2019)
This study aims to calculate and analyze whether or not a decline occurs in regional income inequality (sigma convergence). Additionally, it attempts to examine the ability of low-income provinces to catch up the provinces with a high regional income, neither controlled nor (absolute convergence and conditional convergence). Finally, the study calculates the speed and time needed to catch up to half of the lags. The first objective of thestudy was answered by using the coefficient of variation. The second objective was answered by the First Difference GMM (FD GMM) method, and the third objective was answered by using a formula for calculating the convergence speed expressed by Feldkircher (2006), and the half convergence formula from Barro & Sala-i-Martin (1995). This research figured out that sigma convergence occurreds after divergence. The research also reported no convergence of regional income beta, in both absolute and conditional convergences. Finally, the time needed to catch up the half of the lags in non-conditional beta convergence was shorter than conditional beta convergence. Keywords: Sigma convergence, Absolute convergence, Conditional convergence, Speed of convergence, The life half of convergence JEL Classifications: E6, H7, O1 DOI: https://doi.org/10.32479/ijefi.8689